PRODUCT PERFORMANCE AND SERVICESCAPE COMPARISON BETWEEN STARBUCKS AND COFFEE BEAN IN MANADO TOWN SQUARE - Wongkar, Esther V.; Saerang, David P. E.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Coffee is a type of beverage that is important for most people throughout the world. The high number of Indonesian coffee consumption has led to a development of coffee shops that provide authentic processed domestic coffee. Increasing demand for coffee and coffee drinking trends among the community makes more and more entrepreneurs try to enter the coffee shop business. Starbucks and Coffee Bean is one example of a trendy coffee shop. The main objective of this study is to find out whether there is a comparison of product performance and servicescape at Starbucks and Coffee Bean & Tea Leaf Manado Town Square. This type of research in this research is comparative research. The sample of this research are 100 customers of both Starbucks and Coffee Bean & Tea Leaf in Manado Town Square. The data analysis technique in this study is the comparison test / different test. The results showed that: there were differences in Starbucks product performance and Coffee Bean & Tea Leaf product performance and there were differences in Starbucks servicescape and Coffee Bean & Tea Leaf servicescape. Based on the conclusion of the above research, the things that can be suggested from this study are it is important for Starbucks and The Coffee Bean & Tea Leaf to maintain product performance and develop each product so that its performance is more improved and becomes a differentiator for competing product, and for further researchers it is recommended to increase the scope of research with larger objects. And can proceed to another analysis in the form of multiple regression analysis, path analysis and others.Â Keywords: product performance, servicescape